2019
DOI: 10.1111/jog.14172
|View full text |Cite
|
Sign up to set email alerts
|

Proportion of abnormal second 50‐g glucose challenge test in gestational diabetes mellitus screening using the two‐step method in high‐risk pregnant women

Abstract: Aims:To determine the merit of repeating 50-g glucose challenge test (50-g GCT) at 24-28 weeks of gestation in high-risk pregnant women and the prevalence of early-and late-onset gestational diabetes mellitus (GDM). Methods: This study was conducted in 1447 pregnant women, 344 of them were at risks for GDM undergoing screening by two-step method at first visit. Data were not completely collected in 47 women leaving only 297 for analyses. Fifty-six of 297 pregnant women were diagnosed as early-onset GDM (18.8%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…A large retrospective cohort study in Portugal including 18,518 pregnant women with GDM reported that the incidence of earlyonset GDM (≤12 weeks) was 34.4% according to the IADPSG diagnostic criteria; there was no difference in the incidence of PE between women with early-and later-onset GDM (74). Furthermore, several studies have reported the same conclusion (55, [75][76][77][78][79]. In early-onset GDM, metformin or insulin treatment is more needed (75,78,79), it is uncertain whether it will affect the occurrence of PE.…”
Section: Time Of Gdm Occurrencementioning
confidence: 86%
See 1 more Smart Citation
“…A large retrospective cohort study in Portugal including 18,518 pregnant women with GDM reported that the incidence of earlyonset GDM (≤12 weeks) was 34.4% according to the IADPSG diagnostic criteria; there was no difference in the incidence of PE between women with early-and later-onset GDM (74). Furthermore, several studies have reported the same conclusion (55, [75][76][77][78][79]. In early-onset GDM, metformin or insulin treatment is more needed (75,78,79), it is uncertain whether it will affect the occurrence of PE.…”
Section: Time Of Gdm Occurrencementioning
confidence: 86%
“…Furthermore, several studies have reported the same conclusion ( 55 , 75 79 ). In early-onset GDM, metformin or insulin treatment is more needed ( 75 , 78 , 79 ), it is uncertain whether it will affect the occurrence of PE. However, women with early-onset GDM have more risk factors for PE, such as older age, multiple pregnancy, and higher pre pregnancy BMI ( 80 , 81 ).…”
Section: Factors Associated With Occurrence Of Pe In Women With Gdmmentioning
confidence: 99%
“…From a systematic review of diagnostic test accuracy studies in Southeast Asia, the prevalence of GDM screened using a two-step approach at 24–28 weeks ranged from 7.1% to 28.6% in Thailand [ 37 ]. Two retrospective studies were published in 2020 [ 38 ] and 2021 [ 16 ], which showed the rates of early onset GDM at 18.9% and 9.2%, respectively. The variation in the reported early GDM rate depends on universal screening or screening in high-risk pregnant women.…”
Section: Discussionmentioning
confidence: 99%